Pelatihan Penggunaan Aplikasi Pengelolaan Bank Sampah Dan Laporan Keuangan Berbasis Website Pada Bank Sampah Melati Bersih, Bojonggede, Bogor - Rusiyati, Sri; Handayanna, Frisma; Purnamasari, Indah (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
Clean Melati Waste Bank (BSMB) Atsiri Permai is an institution driving community empowerment in terms of effective waste management as an application of the green economy concept which will provide great benefits for the community's economy and environmental sustainability. BSMB Atsiri Permai activities have been running since 2013 with the motto Clean and Smile Movement starting from 3 R (Reduce, Reuse, Recycle) which is an inorganic waste management technique starting from providing information about how to sort inorganic waste and collect used cooking oil. The aim of this PKM Program is to apply digital technology to the management of BSMB Atsiri Permai RW. 12 to improve BSMB activity services for its customers in obtaining the necessary information anytime and anywhere as well as making it easier to create website-based financial reports. The method used is by providing counseling, training and assistance regarding the use of waste bank management applications and website-based financial reports on BSMB and evaluation by providing questionnaires with indicators of website usability, ease of recording and accessing data, types of information and reports on the Waste Bank website Atsiri Permai. The results of the PkM show that the website-based Waste Bank Application Training is very beneficial for BSMB Atsiri Permai, such as providing activity information that can be accessed at any time and can be widely reached as well as making it easier to record, manage the Waste Bank, report to customers and prepare financial reports to increase transparency. and accountability in fund management. Technology and to minimize recording errors. There has been an increase in understanding and skills in using waste bank management applications and preparing financial reports by 90%.